2020
DOI: 10.1002/brb3.1896
|View full text |Cite
|
Sign up to set email alerts
|

What it takes to be at the top: The interrelationship between chronic social stress and social dominance

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 61 publications
3
11
0
Order By: Relevance
“…An additional factor that likely shapes the relationship between rank and stress susceptibility is the length of group housing prior to testing. Šabanović et al (2020) group-housed mice for two weeks before stress exposure, and in this case, they did not find any differences in stress susceptibility between ranks. This result in conjunction with ours importantly argues against innate resilience in dominants for males, but instead suggests there are advantages gained from both acquiring and maintaining a dominant position.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…An additional factor that likely shapes the relationship between rank and stress susceptibility is the length of group housing prior to testing. Šabanović et al (2020) group-housed mice for two weeks before stress exposure, and in this case, they did not find any differences in stress susceptibility between ranks. This result in conjunction with ours importantly argues against innate resilience in dominants for males, but instead suggests there are advantages gained from both acquiring and maintaining a dominant position.…”
Section: Discussionmentioning
confidence: 72%
“…Our findings stand in contrast to prior work which revealed an opposite pattern of resilience by rank. Previously it has been demonstrated that the most dominant 50% of male mice are more stress susceptible to social defeat (Larrieu et al, 2017), while others have shown no relationship between rank and social stress susceptibility (Šabanović et al, 2020). Closer examination of the social landscape reveals potential explanations for these differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A two-stage social interaction test (SI) was performed in a square arena (40 cm × 40 cm) with artificially defined interaction zone (14 cm × 26 cm) and corner zones (10 cm × 10 cm) as we previously reported in both male and female mice (Takahashi et al, 2017;Šabanović et al, 2020). In the first test (target-absent), the experimental mouse was allowed to freely explore the arena with an empty wire mesh sleeve (10 cm × 6 cm) in the interaction zone.…”
Section: Social Interaction Testmentioning
confidence: 99%
“…Social rank in a group of individuals constantly monitors one’s standing in relation to others and uses that information to guide behavior [ 4 ], such as access to resources and defending territories. Therefore, hierarchical rank has broad effects on physical and mental health due to the risk factors associated with living in a particular rank [ 5 ].…”
Section: Introductionmentioning
confidence: 99%